2012
DOI: 10.1111/j.1365-2435.2012.02023.x
|View full text |Cite
|
Sign up to set email alerts
|

Stoichiometry of potassium is largely determined by water availability and growth in Catalonian forests

Abstract: Summary The study of the relationships between organisms and environmental elemental stoichiometry and ecosystem structure and function has recently received increasing attention. Some elements, however, have been less studied or have even been neglected. One of these elements is K, despite its critical importance in the water economy of plants. We hypothesized that K concentrations and especially K contents (concentrations × biomass), their stoichiometries with respect to C, N, and P contents, and their rel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
63
0
2

Year Published

2013
2013
2019
2019

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 75 publications
(71 citation statements)
references
References 61 publications
3
63
0
2
Order By: Relevance
“…Tomlinson et al (2013), while comparing leaf traits of different plant species growing in wet and arid environments, observed that leaves of species adapted to arid sites are small with high K concentrations. Furthermore, it was observed that tree species at the driest sites, such as in mediterranean evergreen and dry tropical forests, have a higher capacity to change their seasonal internal allocation of K, with a higher allocation of K to leaves during summer (the driest season) than the species at wetter sites (Milla et al, 2005;Rivas-Ubach et al, 2012;Sardans et al, 2012a).…”
Section: K Stoichiometry and Water Availability In Terrestrial Ecosysmentioning
confidence: 99%
See 1 more Smart Citation
“…Tomlinson et al (2013), while comparing leaf traits of different plant species growing in wet and arid environments, observed that leaves of species adapted to arid sites are small with high K concentrations. Furthermore, it was observed that tree species at the driest sites, such as in mediterranean evergreen and dry tropical forests, have a higher capacity to change their seasonal internal allocation of K, with a higher allocation of K to leaves during summer (the driest season) than the species at wetter sites (Milla et al, 2005;Rivas-Ubach et al, 2012;Sardans et al, 2012a).…”
Section: K Stoichiometry and Water Availability In Terrestrial Ecosysmentioning
confidence: 99%
“…Globally, however, plant K uptake appears to be associated with water availability (Sardans et al, 2011(Sardans et al, , 2012aGe et al, 2012), wherein a lower K uptake in turn negatively affects water uptake by reducing the activity of aquaporins (Kanai et al, 2011). All these interconnected relationships strongly suggest a cascade of higher water deficit, lower K uptake and a reduced capacity to avoid drought, which could become a serious problem in currently dry areas that are threatened by future drier scenarios.…”
Section: K In a Drier Worldmentioning
confidence: 99%
“…More retranslocation should thus lead to a low release of N and P from litter and lower availability of soil N and P. The high capacity for erosion of Mediterranean rain may have further favored the evolution of plants toward higher retranslocation to assure better control of nutrient stocks, thereby improving the capacity of the plant-soil system to retain nutrients. The high retranslocation is related to the observed higher percentage of nutrients in the stand biomass of Mediterranean forests compared with other forest types (Rodà et al 1999a, b;Sardans and Peñuelas 2012;Sardans et al 2012a).…”
Section: Plant Cover and Soil Fertility And Water Availabilitymentioning
confidence: 99%
“…These shifts are frequently associated to changes in the structure of plant communities and/or in nutrient outputs (e.g. crop harvesting and weathering) (Sardans et al, 2012a). Land-use changes due to agronomic practices and livestock production generate soil stoichiometric shifts in forests (Falkengren-Gerup et al, 2006;Sardans and Peñuelas, 2013), shrublands , grasslands (Mulder and Elser, 2009) and steppes (Jiao et al, 2013).…”
Section: Introductionmentioning
confidence: 99%